Career transition to become a social entrepreneur: the challenges faced by youth social entrepreneur in Malaysia - Che Nawi, Nur Raihan; Arshad, Mohd Mursyid; Krauss, Steven Eric; Ismail, Ismi Arif (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The practice of social entrepreneurship activities has grown rapidly around the world and as well as in Malaysia; although in Malaysia it is still considered to be in the early stage period. Nevertheless, little is known about the challenges faced among youth that chooses their career as a social entrepreneur. The main goal of this study is to explore what are the challenges faced by youth social entrepreneur that runs a social enterprise in the Malaysian context. This study was conducted using a qualitative approach, where interviewing methods were used for four youth social entrepreneurs who were voluntarily engaged in this study. Findings of this study have shown career transition to become a social entrepreneur such as i) acclimating to life and career as a social entrepreneur and ii) not getting the support from family are the challenges faced by them. This finding has shown that informants have faced challenges that then became a valuable learning process for them in developing their career as a social entrepreneur. In this regard, the researcher has seen that the process of their career development as a social entrepreneur has given meaning to the informants. And despite the many challenges they have faced, social entrepreneurship activity has reinforced the role of youth social entrepreneur especially when it comes to social responsibility.